2013
DOI: 10.1128/mbio.00922-13
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Code of Toxoplasma gondii Comprises Conserved and Unique Posttranslational Modifications

Abstract: Epigenetic gene regulation has emerged as a major mechanism for gene regulation in all eukaryotes. Histones are small, basic proteins that constitute the major protein component of chromatin, and posttranslational modifications (PTM) of histones are essential for epigenetic gene regulation. The different combinations of histone PTM form the histone code for an organism, marking functional units of chromatin that recruit macromolecular complexes that govern chromatin structure and regulate gene expression. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(124 citation statements)
references
References 60 publications
(100 reference statements)
9
114
1
Order By: Relevance
“…AAL binding is also found in proximity to euchromatin (Fig. S7C), as defined by antibodies against two histone modifications associated with active transcription, H3K9Ac and H3K4Me3 (9). Last, two predicted FG-NupsNup68, which is enriched by AAL, and Nup67, which is not-were expressed with a C-terminal YFP under their endogenous promoters ( Fig.…”
Section: O-fucosylation Directs Glycoproteins To Aal-labeled Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…AAL binding is also found in proximity to euchromatin (Fig. S7C), as defined by antibodies against two histone modifications associated with active transcription, H3K9Ac and H3K4Me3 (9). Last, two predicted FG-NupsNup68, which is enriched by AAL, and Nup67, which is not-were expressed with a C-terminal YFP under their endogenous promoters ( Fig.…”
Section: O-fucosylation Directs Glycoproteins To Aal-labeled Assembliesmentioning
confidence: 99%
“…Transcriptome analyses have revealed that a large percentage of mRNAs show life stage-specific expression (4) and/or cell cycle regulation (5). Recent studies have increased our understanding of gene expression in T. gondii by identifying the AP2 family of transcription factors (6)(7)(8) and by describing posttranslational modifications (PTMs) of histones and some of the enzymes responsible for them (9)(10)(11). However, little is known about protein organization at the nuclear periphery, a subnuclear compartment that plays a critical role in transcriptional regulation in many eukaryotes.…”
mentioning
confidence: 99%
“…H2A.Z and H2B.Z have been shown to be hyper-acetylated in the N-terminal [30]. Acetylation is one of the most prominent modifications influencing gene expression [31, 32] as neutralization of the positively charged histone N-terminal tails leads to chromatin decondensation, thereby enhancing transcriptional activity [32].…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation is one of the most prominent modifications influencing gene expression [31, 32] as neutralization of the positively charged histone N-terminal tails leads to chromatin decondensation, thereby enhancing transcriptional activity [32]. In other organisms, as well as T. gondii , H2A.Z with its hyperacetylated N-terminal region, is preferentially present in regions of the genome correlating with transcriptional activation [33], and this should also be true for H2B.Z, where the N-terminal tail is acetylated on lysines 3, 8, 13, 14, and 18 [30]. Similar results were also observed in P. falciparum [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the post-translational modifications of histones was conducted by combining two protocols (Nardelli et al, 2013;Shechter et al, 2007). Embryos of the specified developmental stage ( preDII, DII, postDII; 18-36 dpf ) were collected and rinsed in 0.03% hypochlorite for 5 min to remove external chorionic debris and microorganisms, and then rinsed once with diH 2 O.…”
Section: Acid Extraction Of Histonesmentioning
confidence: 99%